CSS3 and SVG with Perplexity - Campesato, Oswald (Mercury Learning and Information, 2024)
Cover -- Title -- Copyright -- Dedication -- Contents -- Preface -- Chapter 1 The Generative AI Landscape -- What is Generative AI? -- Important Features of Generative AI -- Popular Techniques in Generative AI -- What Makes Generative AI Different -- The Successes of Generative AI -- Conversational AI Versus Generative AI -- Primary Objective -- Applications -- Technologies Used -- Training and Interaction -- Evaluation -- Data Requirements -- Is DALL-E Part of Generative AI? -- Are ChatGPT-3 and GPT-4 Part of Generative AI? -- Artificial General Intelligence Versus Generative AI -- Generative AI Versus ML, DL, NLP, and RL -- Which Fields Benefit the Most from Generative AI? -- How Will the Enterprise Space Benefit from Generative AI? -- The Impact of Generative AI on Jobs -- What is Artificial General Intelligence (AGI)? -- When Will AGI Arrive? -- How Can We Prepare for AGI? -- Will AGI Control the World? -- Should Humans Fear AGI? -- Beyond AGI -- DeepMind -- DeepMind and Games -- Player of Games (PoG) -- OpenAI -- Cohere -- Hugging Face -- Hugging Face Libraries -- Hugging Face Model Hub -- AI21 -- Anthropic and Claude 3 -- Advantages of Claude 3 -- Limitations of Claude 3 -- Is Claude 3 Part of Generative AI? -- Llama 3 -- What is Perplexity? -- Perplexity Versus Google Search -- What is Meta AI? -- What are LLMs? -- What is the Purpose of LLMs? -- Model Size Versus Training Set Size -- Do LLMs Understand Language? -- Caveats Regarding LLMs -- Pitfalls of Working with LLMs -- A Brief History of Modern LLMs -- Aspects of LLM Development -- LLM Size Versus Performance -- Emergent Abilities of LLMs -- Kaplan and Under-Trained Models -- Real-World Use Cases for Generative AI -- Sunmmary -- Chapter 2 Prompt Engineering -- What is Prompt Engineering? -- Prompts and Completions -- Types of Prompts -- Instruction Prompts -- Reverse Prompts.
Keywords: Cascading Style Sheets 3.0; SVG